Longitudinal associations between Big Five personality and insomnia: evidence based on a 4-year perspective cohort study among community residents - Ziming Shao; Ziming Shao; Zhen Wei; Zhen Wei; Meiqi Wang; Meiqi Wang; Yifan Chen; Yifan Chen; Yazhuo Qi; Yazhuo Qi; Zihan Zhou; Zihan Zhou; et al. (Frontiers in Psychology)
IntroductionWhile the association between personality traits and insomnia has been confirmed, the longitudinal relationship between them remains unclear.MethodsThis is a 4-year longitudinal cohort study conducted among rural community residents (N = 482) in Shandong Province, China.ResultsThis study found that neuroticism (β = 0.175, p < 0.001), extraversion (β = −0.146, p < 0.001), and conscientiousness (β = −0.168, p < 0.001) at baseline had statistically significant longitudinal associations with insomnia at follow-up. In addition, insomnia at baseline had statistically significant longitudinal correlations with neuroticism (β = 0.142, p < 0.01), extraversion (β = −0.209, p < 0.001), and agreeableness (β = −0.122, p < 0.01) at follow-up.DiscussionThis study showed that both neuroticism and extraversion had a bidirectional relationship with insomnia. Insomnia had a one - way longitudinal correlation with agreeableness, and conscientiousness had a one - way longitudinal correlation with insomnia. The longitudinal correlation between openness and insomnia was not supported in this study.